ARTICLE REVIEW: KLASIFIKASI DAN TATALAKSANA RETINOPATI PREMATURITAS - Cholyviona W.S Handhayani; Putu Ristyaning Ayu Sangging; Rani Himayani (CV. Jasa Sukses Abadi, 2023)
Retinopathy of Prematurity (ROP) is a condition or illnesses of the retina that frequently affects infants. Retinopathy of Prematurity is an abnormal development of blood vessels in the eye which typically affects infants born prematurely. Premature Retinopathy is a condition that affects many nations on a global scale, with an expected incidence of over 45 cases for every 100,000 pregnancies. According to the International Classification of Retinopathy of Prematurity (ICROP), there are five stages of the disease based on the severity and three zones of retinal development based on where they form. The retina is the innermost layer of the eyeball that receives light and transmits it to the brain, allowing us to see distinctly. Disturbances in the retina can produce visual disturbances. As a result, any visual disturbances must be treated promptly and precisely. Cryotherapy, laser photocoagulation, anti-VEGF drugs, and vitrectomy healing measures at an advanced level are treatments that can be used in instances of Premature Retinopathy in premature babies. This writing employs the article review technique, with sources sourced from journals and books. This writing seeks to discover the definition, classification, and treatment of Premature Retinopathy, with the hope of improving standards and quality of care for Premature Retinopathy.